Cyber Branding Rumah Budaya Kratonan dalam Membentuk Citra Community Center Kota Surakarta - Syahroi, Muhammad Ridwan; Briyan Pratiwi, Rhesa Zuhriya (Fakultas Ekonomi dan Ilmu Sosial Program Studi Ilmu Komunikasi Universitas AMIKOM Yogyakarta, 2024)
This article aims to describe the cyber branding of Rumah Budaya Kratonan (RBK) as a community center via Instagram @rumah_kultur_kratonan. The type of research is descriptive qualitative, data collection through observation, in-depth interviews, and documentation of relevant sources. Data analysis was prepared interactively and source triangulation was carried out to find the validity of the data. The theory used is cyber branding in the 3